THE COGNITIVE BENEFITS OF BILINGUALISM AND MULTILINGUALISM ON BRAIN DEVELOPMENT - Meyliqulov Zidan (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Multilingualism research shows unique properties of multilinguals, including early language representation, gray matter density, and lexical retrieval speed. Cognitive control, language switching, working memory, and consequences of multilingualism are reviewed. Structural differences exist between monolinguals and multilinguals' brains with different regions used for processing a given language in multilinguals compared to monolinguals.